Våld som kontroll, hämnd eller försvar: Kön och makt i balladens universum - Åkesson, Ingrid (Puls – musik- och dansetnologisk tidskrift, 2022)
This article analyses the universe of the traditional ballad from a perspective that problematizes gender power relations and masculinity. This universe is generally characterised by masculine domination, separation of male and female spheres, and manifest structures of power. Masculine violence, not least sexual violence, tends to be normative, especially in heroic ballads and ballads of chivalry, although other masculinities also exist. Feminine power is usually circumscribed, and feminine violence is accepted only under certain conditions. Several narrative motifs concerning masculinity, femininity, violence and power structures can be traced across different ballad types. The author analyses some of these motifs, and clusters of motifs, using the methods of re-reading, close reading and cross-reading. Examples are taken from the Scandinavian and English-Scottish ballad corpora.